ENHANCING STUDENTS’ LEARNING ACHIEVEMENT - Lestari, Viviana Lisma; Suwarsito, Suwarsito (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This study aims to: determine whether there is a positive influence and significant correlation between the learning environment and learning motivation either alone or together on student achievement Al Lughah . The population in this study is Al-Lughah students totaling 180 students with an error level of 5%, the samples of 120 students are obtained using random sampling techniques. The data collection instrument uses a questionnaire that has been tested for validity and reliability. Data analysis uses multiple regression analysis. The results of the regression analysis concludes that (1) There is a positive and significant influence between parental attention on learning achievement t count = 9.355 and t table = 1.876, sig 0.000). (2) There is a positive and significant influence between the learning environment on learning achievement t count = 2.513 and t table = 1.980, sig 0.000). (3) There is a positive and significant influence between the learning environment and parental attention together on learning achievement F = 5,439 and t; Ftable = 3.07, sig 0.000